High-Quality Time Stretch and Pitch Shift Effects for Speech and Audio Using the Instantaneous Harmonic Analysis. (30th November 2010) - Azarov Azarov, Elias Elias; Petrovsky Petrovsky, Alexander Alexander; Parfieniuk Parfieniuk, Marek Marek
Abstract : The paper presents methods for instantaneous harmonic analysis with application to high-quality pitch, timbre, and time-scale modifications. The analysis technique is based on narrow-band filtering using special analysis filters with frequency-modulated impulse response. The main advantages of the technique are high accuracy of harmonic parameters estimation and adequate harmonic/noise separation that allow implementing audio and speech effects with low level of audible artifacts. Time stretch and pitch shift effects are considered as primary application in the paper.